Combination of pulse signal modulation and hydrophilic treatment of a substrate for controlling the thermal distribution in surface acoustic wave atomization. (25th June 2023) - Gai, Chenhui; Hu, Hong; Han, Junlong; Lei, Yulin; Ning, Jia; Ye, Diyi
Highlights: We propose a novel method to control thermal distribution during SAW atomization. It includes pulse signal modulation and hydrophilic treatment of substrates. The highest temperature drops approximately 50℃ during SAW atomization. The method raises the particle diameters of atomization lightly. Abstract: Owing to the temperature limitations of biochemical or biomedical atomization applications, temperature control within a surface acoustic wave (SAW) atomizer is critical. This paper presents a method for controlling the thermal distribution of SAW atomization. This method combines pulse signal modulation and hydrophilic treatment of an SAW substrate. By setting the duty factor to 50 % and contact angle to 30°, the temperature reduces to about 99.3 °C for water and approximately 68.4 °C for a 50 wt% alcohol/water binary mixture during SAW atomization. Therefore, the proposed method effectively controls the thermal distribution during SAW-based atomization. In addition, the particle diameters of the different liquids used for SAW atomization are explored using this method. The results reveal that the general method increases the particle diameters of tiny droplets from 5 μm to 10 μm. Notably, this is within an acceptable range, hence the method has lower effects on the atomization particle diameter.